Հուզական ինտելեկտի զարգացումը կրտսեր դպորացականների դասագրքերում - Հայրապետյան, Գ.
Одна из составляющих эмоциональной культуры - эмоциональный интеллект. Эмоциональный интеллект формулируется как умение понимать свои и чужие эмоции и управление ими. Эмоциональный интеллект необходимо развивать и совершенствовать, чтобы человек мог самоутвердиться в окружающей его действительности. В реализации этой задачи большой вклад имеют уроки родного языка, которые способствуют развитию эмоционального интеллекта у школьников младших классов. One of the components of the emotional culture is the emotional intellect. It is defined as an ability to understand your and other people’s emotions and control them. One should develop and improve one’s emotional intellect in order to assert oneself in the surrounding reality. Native Language lessons play a great role in the accomplishment of this task and contribute to the development of the emotional intellect of the juniors.
Keywords: Հոգեբանություն; Մանկավարժություն